(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The vision of the administration under Goodluck Jonathan is packaged in Transformation Agenda which is aimed at holistic overhaul of every segment of national life. Members of the legal profession have a critical role to play towards the success of the transformation agenda. However, a lawyer can only be as good as the system of legal education that produced him; hence the need to revive and reposition the legal education framework. The paper discussed the responsibility of academic law libraries in the shaping of legal practitioners and towards the academic community. It x-rayed the challenges facing these libraries and made recommendations for improved law library services in Nigeria.